Simultaneous trabeculectomy and cataract extraction. Issue 4 (April 1982) - Romem, M.; Isakow, I.; Dolev, Z.
Abstract : A combined trabeculectomy and cataract extraction was performed on 46 eyes of 39 patients. The average follow-up period was of 27 months. The intraocular pressure remained controlled without the need of postoperative medication in 33 eyes (71.74%); 12 eyes (26.09%) needed further medical treatment; and in one eye the pressure remained uncontrolled and further surgery was necessary. After surgery the visual acuity improved considerably and the complications were few. The combined procedure has many advantages. The patient is cured by one surgical procedure, his visual acuity improves, his intraocular pressure is reduced to normal, and he is relieved from the need for medication postoperatively. By a single stay in hospital and by reducing the number of postoperative medical routine controls the expenses are reduced considerably. Owing to these advantages the combined procedure deserves to be considered in cases of glaucoma and cataract.